Major and Trace Element Geochemistry of the Permian-Triassic Boundary Section at Meishan, South China - Dudás, Francis Ö.; Zhang, Hua; Shen, Shu-Zhong; Bowring, Samuel A. (Frontiers in Earth Science, 2021)
We report extensive major and trace element data for the Permo-Triassic boundary (PTB) at Meishan, China. Analyses of 64 samples from a 2.5 m section span the last 75 kyr of the Permian and the first 335 kyr of the Triassic, from beds 24 to 34. We also report data for 20 acetic acid extracts that characterize the carbonate fraction. Whole rock major element data reflect the change of lithology from carbonate in the Permian to mudstone and marl in the Triassic, indicate an increase of siliciclastic input and MgO in and above the extinction interval (beds 24f - 28), and silica diagenesis in carbonates below the extinction horizon. Above bed 27, enrichment factors calculated with respect to Al and Post-Archean Australian Shale (PAAS) are ~ 1 for most trace elements, confirming that siliciclastic input dominates trace element distributions in the Triassic. Within the extinction interval, beds 24f and 26 show increases in As, Mo, U and some transition metals. V, Cr, Co, Ni, Cu, Zn, Pb, and Ba are variably enriched, particularly in bed 26. Below the extinction interval, the top of bed 24d shows enrichment of V, Cr, Co, Ni, Cu, Zn, Pb, and Ba in a zone of diagenetic silicification. Trace elements thus reflect siliciclastic input, diagenetic redistribution, and responses to redox conditions. Trace element patterns suggest either a change in provenance of the detrital component, or a change in the proportion of mechanical to chemical weathering that is coincident with the beginning of the extinction in bed 24f. Ba, Zr, and Zn behave anomalously. Ba shows little variation, despite changes in biological activity and redox conditions. The enrichment factor for Zr is variable in the carbonates below bed 24f, suggesting diagenetic Zr mobility. Zn shows a sharp drop in the extinction horizon, suggesting that its distribution was related to phytoplankton productivity. Rare earth element content is controlled by the siliciclastic fraction, and carbonate extracts show middle rare earth enrichment due to diagenesis. Ce and Eu anomalies are not reliable indicators of the redox environment at Meishan.